PENINGKATAN PEMAHAMAN KONSEP FISIKA DASAR MELALUI KONFLIK KOGNITIF DENGAN PERTANYAAN TAK TERDUGA - Ronodirdjo, Muhammad Zuhdi; Makhrus, Muh (Kappa Journal, 2020)
Inter-Semester Lectures are identical students whose level of mastery of concept skills is still low. Efforts that can be made to improve students' mastery of concepts are applying learning with the cognitive conflict approach. Students have a very low understanding of concepts in basic physics subjects in temperature and heat. The purpose of this study is to improve the mastery of the concept of students in the material Temperature and Heat. This type of research is a quasi-experimental design with the One Group Pretest-Posttest Design. The sample in this study used students of physics education study programs at one of the universities in NTB. The number of samples in this study was 20 students. The research instrument used was a multiple-choice question. Improved understanding of concepts was analyzed by the N-Gain test. The results showed an increase in mastery of the concept of material temperature and heat after learning with the cognitive conflict approach with an average N-Gain of 0.62 in the medium category